2018
DOI: 10.18087/cardio.2018.9.10147
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Myocardial Hypertrophy as a Result of Arterial Hypertension Among Mountain Shoria Population. The Role of Genetic Polymorphism

Abstract: исследовательский институт комплексных проблем сердечно-сосудистых заболеваний», Кемерово, Россия 2 «НГИУВ»-филиал ФГБОУ ДПО «Российская медицинская академия непрерывного профессионального образования» Минздрава России, Новокузнецк, Россия 3 «Научно-исследовательский институт терапии и профилактической медицины»-филиал ФГБНУ «Федеральный исследовательский центр Институт цитологии и генетики» СО РАН, Новосибирск, Россия Гипертрофия миокарда левого желудочка при артериальной гипертензии у населения Горной Шории.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
(24 reference statements)
1
4
0
Order By: Relevance
“…Recent studies have pointed out an unfavorable course of arterial hypertension in European ethnic minority populations compared to host populations 1 , 2 . A similar situation is observed when examining ethnic minority populations in other regions, for example, in Russian Siberia 3 , 4 . To improve treatment and control rates and reduce differences between populations, it is necessary to identify the determinants of these rates across ethnic groups, and to develop and implement ethnicity-specific intervention strategies, which ultimately help reduce ethnic disparities in hypertension-related complications 2 .…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…Recent studies have pointed out an unfavorable course of arterial hypertension in European ethnic minority populations compared to host populations 1 , 2 . A similar situation is observed when examining ethnic minority populations in other regions, for example, in Russian Siberia 3 , 4 . To improve treatment and control rates and reduce differences between populations, it is necessary to identify the determinants of these rates across ethnic groups, and to develop and implement ethnicity-specific intervention strategies, which ultimately help reduce ethnic disparities in hypertension-related complications 2 .…”
Section: Introductionsupporting
confidence: 71%
“…It was previously shown that different ethnic groups of rural Gornaya Shoriya residents had different genetic associations with LV hypertrophy. At the same time, LV hypertrophy among hypertensive patients was more prevalent in the Shor group than in the non-indigenous (Caucasian) group 4 . In the previous study, no genetic associations with the state of the right ventricle were studied, however, in our study, there were no ethnic differences in the severity of LV hypertrophy.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Recent studies have pointed out an unfavorable course of arterial hypertension in European ethnic minority populations compared to host populations [1,2]. A similar situation is observed when examining ethnic minority populations in other regions, for example, in Russian Siberia [3,4]. To improve treatment and control rates and reduce differences between populations, it is necessary to identify the determinants of these rates across ethnic groups, and to develop and implement ethnicity-speci c intervention strategies, which ultimately help reduce ethnic disparities in hypertension-related complications.…”
Section: Introductionmentioning
confidence: 65%
“…Changes in the structure and function of the heart may not only be caused by genetic characteristics of a particular ethnic group, but also by peculiarities of the lifestyle (for example, traditional lifestyle of ethnic groups), living conditions (countryside / city, highlands / plain), as well as in uence of pathological conditions. Previous studies have studied the features of echocardiography in representatives of two ethnic groups of the Gornaya Shoria region -the indigenous population (Shors) and the non-indigenous population (Caucasians) living both in rural areas [3,4] and in the city [21], (Sumin et al, in press). While the ethnic differences in left ventricular echocardiographic parameters were studied both for healthy urban residents of these groups [21] and for patients with arterial hypertension (Sumin AN, in press), the indicators of the right ventricle were only compared in healthy individuals [21].…”
Section: Introductionmentioning
confidence: 99%